Apoptosis gene profiling reveals spatio-temporal regulated expression of the p53/Mdm2 pathway during lens development. - WRIDE, MICHAEL; MANSERGH, FIONA (My University, 2009)
Evidence is emerging for apoptosis gene expression in the lens during development. Therefore, here we used a filter array to assess expression of 243 apoptosis-related genes in the developing postnatal mouse lens using (33)P labelled cDNA synthesized from p7 and p14 mouse lenses. We demonstrated that 161 apoptosis-related genes were expressed at levels significantly above background and 20 genes were potentially significantly differentially expressed (P<0.05) by at least 2-fold between p7 and p14. We used RT-PCR to confirm expression of these genes in newborn, p7, p14 and 4 wk mouse lens cDNA samples. Expression of 19/20 of the genes examined was confirmed, while 5 genes (Huntingtin, Mdm2, Dffa, galectin-3 and Mcl-1) were confirmed as differentially regulated between p7 and p14. RT-PCR was also used to examine the expression of the chick homologues of the most-highly expressed and/or potentially differentially regulated genes in chick embryo lenses at E6-E16. The majority of genes expressed in the postnatal mouse lens were also expressed in the chick embryo lens. Western blotting confirmed developmentally regulated expression of Axl and Mcl-1 during mouse lens development and of Mdm2, Mdm4/X and p53 during mouse and chick lens development. Western blotting also revealed the presence of p53 and Mdm4/X splice variants and/or proteolytic cleavage products in the developing lens. Since Mdm2 is a regulator of the tumour suppressor gene p53, we chose to thoroughly investigate the spatio-temporal expression patterns of p53, Mdm2 and the functionally related Mdm4/X in mouse lens development at E12.5-E16.5 using immunocytochemistry. We also examined Mdm2 expression patterns during chick lens development at E6-E16 and Mdm4/X and p53 at E14. Expression of Mdm2, Mdm4/X and p53 was spatio-temporally regulated in various compartments of the developing lens in both mouse and chick, including lens epithelial and lens fibre cells, indicating potential roles for these factors in regulation of lens epithelial cell proliferation and/or lens fibre cell differentiation This study provides a thorough initial analysis of apoptosis gene expression in the postnatal mouse lens and provides a resource for further investigation of the roles in lens development of the apoptosis genes identified. Furthermore, building on the array studies, we present the first spatio-temporal analysis of expression of p53 pathway molecules (p53, Mdm2 and Mdm4/X) in both developing mouse and chick lenses, suggesting a potential role for the p53/Mdm2 pathway in lens development, which merits further functional analysis.
PUBLISHED
Keywords: apoptosis gene expression